Aspirantura in Russian Federation: New Approaches - O V Andreeva (Vestnik RUDN International Relations, 2012)
In the context of new approaches in education in the Russian Federation and because of public discussion, concerning the project of the federal law on education a new format of typical educational standard for doctoral studies based on Russian universities is proposed.